Very Early In-Utero Diagnosis of Walker-Warburg Phenotype: The Cutting Edge of Technology - Achiron, R.; Katorza, E.; Reznik-Wolf, H.; Pras, E.; Kidron, D.; Berkenstadtt, M. (Ultrasound International Open, 2016)
Walker-Warburg phenotype is a severe and lethal autosomal recessive disorder, belonging to a group of congenital malformations defined as abnormal pial basement membrane formation. So far, prenatal diagnosis was considered possible only during late pregnancy.First trimester assessment of a pregnancy suspected to be affected by Walker-Warburg phenotype, using a high-resolution transvaginal ultrasound probe (6–12 MHz), T2 MR imaging (1.5T), molecular genetics and histopathology.Very early diagnosis of the Walker-Warburg phenotype at 11 weeks of gestation proved possible by depicting the classic signs of this entity, confirmed by molecular genetics, post-abortion MR imaging and histopathology.Advancements in ultrasound equipment and technology, molecular genetics and histopathology have made very early detection of this syndrome possible, thus shedding new light on the natural history of this malformation.
Keywords: walker-warburg phenotype; prenatal diagnosis; advanced technology; transvaginal ultrasound; ultrasound; obstetrics